Analisis Getaran pada Plat Komposit Berlapis dengan Higher Order Shear Deformation Theory - Arifi, Eva; Suseno, Hendro; Argo, Dwi (Rekayasa Sipil, 2010)
The application of laminated composite plate as a structural plate element has been increasingly fast because of their high strength and stiffness properties, light weight, and low unit cost. The application of laminated composite plate needs high accuracy and efficiency in vibration analysis of such structure. A dynamic response to time depended loads can caused damage of the structure.There are three theories of plate have been developed. The first is Classical Plate Theory (CPT) which has a weakness by neglected transverse shear deformation effect. The second is First Order Shear Deformation Theory (FOSDT). This theory accounts for transverse shear deformation, but still need a shear correction factor. In order to overcome this problems, a higher order shear deformation theory was developed. This teory accounts for the transverse shear deformation with a parabolic variation of transverse shear strains throughout the thickness, and the zero transverse shear stress on the surfaces of the plates. There is no need to use shear corrrection factor. HOSDT models gives high accuracy for thin and thick plate, anisotropic and isotropic materials. The purpose of this research is to find the natural frequencies of laminated composite plate for varying thickness, fiber angle, lamina thickness, the number of lamination, and support conditions.Analysis result shows that for lamination composite plate, the natural frequencies depend on length to thickness ratio (a/h) of the plate, fiber angle, lamina thickness, the number of lamination, and support conditions. The decrease of the natural frequencies compares to the increase of the length to thickness ratio (a/h). It is influenced the stiffness of the properties. The affect of support condition shows for hinged condition gives bigger natural frequency compares to simply supported laminated composite plate for the same angle fiber.Â